Analysis of Learning Interest, Level of Discipline, and Student’s Responsibility for Post Covid-19 Learning Outcomes - Kusmiati, Kusmiati; Ahyani, Nur; Fitria, Happy (Yayasan Sembilan Pemuda Indonesia, 2024)
The COVID-19 pandemic significantly impacted various aspects of life, including education, lifestyle, habits, and social behavior. Online learning at SMA Negeri 1 Jebus faced unstable conditions and limited signal, leading to low discipline and responsibility among students. This decreased interest in learning and quality of education was analyzed in 2021/2022 to understand the impact on post-Covid-19 learning outcomes. This problem made the author analyze students’ interest in learning, level of discipline, and responsibility for post-COVID-19 learning outcomes at SMA Negeri 1 Jebus, West Bangka Regency in 2021/2022. This research uses quantitative methods with a correlational type of research because this research aims to see the relationship between one variable and another variable. In this study, the population was all students at SMA Negeri 1 Jebus, totaling 715 students from class X to class XII. This sample will be taken from class XI students. In this research, the data collection techniques that researchers used were questionnaires and documentation. Based on this research, the results were obtained The study found that interest in learning, discipline, and responsibility significantly influenced post-Covid-19 learning outcomes at SMAN 1 Jebus, West Bangka Regency. The variables of interest in learning, discipline, and responsibility had a positive impact, with the remaining variables being 0.288 or 28.8%. The adjusted R square figure is 0.712 or 71.2%.